2016
DOI: 10.1038/srep24748
|View full text |Cite
|
Sign up to set email alerts
|

Role of Berberine in the Treatment of Methicillin-Resistant Staphylococcus aureus Infections

Abstract: Berberine is an isoquinoline alkaloid widely used in the treatment of microbial infections. Recent studies have shown that berberine can enhance the inhibitory efficacy of antibiotics against clinical multi-drug resistant isolates of methicillin-resistant Staphylococcus aureus (MRSA). However, the underlying mechanisms are poorly understood. Here, we demonstrated that sub-minimum inhibitory concentrations (MICs) of berberine exhibited no bactericidal activity against MRSA, but affected MRSA biofilm development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 49 publications
5
74
1
Order By: Relevance
“…This compound altered bacterial DNA synthesis. It also hinders the biofilm formation of methicillin-resistant S. aureus (MRSA) in a concentration-dependent manner ranging from 1 to 64 μg/mL via inhibiting phenolsoluble modulins (PSMs) aggregation into amyloid fibrils (Chu et al, 2016).…”
Section: Effect Against Neurodegenerative Diseasesmentioning
confidence: 99%
“…This compound altered bacterial DNA synthesis. It also hinders the biofilm formation of methicillin-resistant S. aureus (MRSA) in a concentration-dependent manner ranging from 1 to 64 μg/mL via inhibiting phenolsoluble modulins (PSMs) aggregation into amyloid fibrils (Chu et al, 2016).…”
Section: Effect Against Neurodegenerative Diseasesmentioning
confidence: 99%
“…BBR is one of the commonly used drugs in the treatment of intestinal infections in China [6]. In addition to its broad spectrum bacteriostatic effects [7][8][9], BBR is reported to have anti-inflammatory, anti-oxidant, anti-tumor, hypoglycemic and anti-cardiac arrhythmia qualities [10][11][12][13][14]. Studies also reported that BBR had good bacteriostatic effect on E. coli and Bacillus subtilis [15].…”
Section: Berberine (Bbr) Is the Main Component Of The Traditional Chimentioning
confidence: 99%
“…Subsequent studies reported that the MIC of BBR against the MRSA reference strain ATCC33591 was 128 µg/mL. BBR can affect the aggregation of amyloid fibers in PSMs of MRSA biofilm, thus inhibiting the formation of MRSA biofilm and increasing the bactericidal activity of antibiotics [9]. Recent studies have reported that BBR had bacteriostatic effects on MRSA, yet no specific study on its bacteriostatic mechanism has been reported.…”
Section: Berberine (Bbr) Is the Main Component Of The Traditional Chimentioning
confidence: 99%
See 1 more Smart Citation
“…Cortex and Coptis chinensis Franch and fully chemically synthesized now [14], has been widely used to treat bacterial diarrhea and gastroenteritis for many years in China [15,16]. Several studies have demonstrated the antibacterial activities of berberine alone or as a synergist of antibiotics [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%